148 The influence of kudzu (Pueraria montana var. lobata) age on in situ rumen degradation. (29th July 2019) - Gulizia, Joseph; Downs, Kevin; Cui, Song
Abstract: Early and late season kudzu (Pueraria montana var. lobata) leaves were collected to analyze dry matter (DM), crude protein (CP), acid detergent fiber (ADF), and neutral detergent fiber (NDF) in situ rumen disappearance to assess kudzu quality. Four studies were conducted during different growing seasons [2 repeated early season (ES); 2 repeated late season (LS) to determine age variability effects. Kudzu collected from 7 middle Tennessee counties were incubated in the rumen for designated lengths of time (0.25, 1, 12, 24, 36, 48, and 72 h) to determine total rumen degradation (%) and rate of disappearance (% / h). Data were analyzed as a randomized complete block design (RCBD) with repeated measures. Regression analysis was used to determine degradation rate. Overall season effects (across incubation times) for dry matter disappearance (DMD) were significantly different (P < 0.0001). Significant season by incubation time interactions were exhibited for total DMD at 12 (P < 0.0001), 24 (P = 0.0004), 36 (P = 0.0055), 48 (P = 0.0209), and 72 h (P = 0.0384) incubation, with an average rumen degradability of ES kudzu being 9.75% higher than LS between 12 and 72 h. Slope regression between 1 and 24 h determined a rumen degradation rate of 2.41% / h across both seasons, with no significant seasonal difference (P = 0.3396). These results are indicative that ES kudzu is more highly rumen degradable than LS, as evidenced by the significant season by incubation time interactions between 12 and 72 h of incubation. Although there are significant seasonal effects on kudzu DMD during certain incubation times, DMD overall for ES and LS is still indicative of high rumen degradability with an average of 81.45% at 72 h across both seasons. Season effects were minimal for NDF, ADF, and CP rumen disappearance.